1995
DOI: 10.3109/07435809509030467
|View full text |Cite
|
Sign up to set email alerts
|

Studies of the guinea pig adrenal cytochrome P450c17 cDNA

Abstract: Cytochrome P450c17 is a single enzyme that catalyzes two successive reactions within the delta 5 and delta 4 pathways. The proteins expressed with human, bovine, and rat cDNAs convert both pregnenolone and progesterone into delta 5-delta 4-C19 steroids, although the rat cDNA prefers the delta 4 pathway. Our results showed that the guinea pig adrenal possesses the enzymatic machinery to produce C19 steroids and suggest that the lyase activity plays a major role in regulating these syntheses. To obtain more info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
7
2
Order By: Relevance
“…This result differs from the earlier report (Tremblay et al, 1995) using COS-1 cells transfected with the cDNA for guinea pig P450c17 where P4 was reported to be 17α-hydroxylated more rapidly than P5. In addition, there was the unexplained difference that a small but measurable amount of DHEA is formed from P5 using the transfected COS-1 cell system (Tremblay et al, 1995). No DHEA was detected in the present study using the purified fusion protein assay in the presence or absence of added b 5 .…”
Section: P4 and P5 Metabolism By The Guinea Pig 17a-hydroxylase Fusiocontrasting
confidence: 85%
“…This result differs from the earlier report (Tremblay et al, 1995) using COS-1 cells transfected with the cDNA for guinea pig P450c17 where P4 was reported to be 17α-hydroxylated more rapidly than P5. In addition, there was the unexplained difference that a small but measurable amount of DHEA is formed from P5 using the transfected COS-1 cell system (Tremblay et al, 1995). No DHEA was detected in the present study using the purified fusion protein assay in the presence or absence of added b 5 .…”
Section: P4 and P5 Metabolism By The Guinea Pig 17a-hydroxylase Fusiocontrasting
confidence: 85%
“…Furthermore, even in the presence of cytochrome b 5 , the rate of the 17,20-lyase activity remains lower than that of the hydroxylase activity and is usually preferentially enhanced in either the ⌬4 or the ⌬5 pathway. For instance, in small animals, such as rats (21), mice (22), hamsters (23), and guinea pigs (24), CYP17 is more active in the ⌬4 pathway. In contrast, human and primate CYP17s utilize the ⌬5 pathway (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…For example, corticosterone is the major glucocorticoid produced in rats and mice, whereas cortisol is the major glucocorticoid in the human, monkey, cow, rabbit, hamster and the guinea pig. This is due to the fact that guinea pigs, like humans, but unlike mouse and rat, express P450c17 and make C 19 steroids within their adrenals [19]. Due to these characteristics, the guinea pig becomes an appropriate in vivo model to study the mechanisms involved in adrenal steroidogenesis.…”
Section: Discussionmentioning
confidence: 98%
“…While corticosterone is the glucocorticoid produced in rats and mice, due to the lack of adrenal P450c17 expression, cortisol represents the major glucocorticoid in guinea pig, as in humans [19]. Although DHEA and dehydroepiandrosterone sulfate (DHEAS), being the major circulating C 19 steroids in humans, are not detected in the guinea pig circulation, it has been demonstrated that another C 19 steroid, namely 11beta-hydroxyandrostenedione (11␤-OHDIONE), is produced by the guinea pig adrenals and that the levels of circulating 11␤-OHDIONE could be stimulated after administration of adrenocorticotropic hormone (ACTH) [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%